Legal Analysis of Forged Property Rights Certificates Used as Collateral by Banks - Wimbo Bintoro; Yoyok Ucuk Suyono; Subekti Subekti; M. Yustino Aribawa; Bachrul Amiq (CV. AFDIFAL MAJU BERKAH, 2026)
The use of land title certificates (Sertifikat Hak Milik/SHM) as collateral in Indonesian banking practices faces a significant legal and institutional gap due to the proliferation of counterfeit documents. This study investigates the normative inadequacies that fail to protect bona fide creditors from the consequences of forged SHM. Using a normative juridical method, this doctrinal legal research analyzes statutory instruments, case law, and legal doctrines, particularly Government Regulation No. 24/1997, Law No. 10/1998, and the Basic Agrarian Law. Findings reveal persistent structural weaknesses in certificate verification systems, institutional fragmentation, and a lack of preventive legal frameworks. The absence of electronic authentication mandates, strict liability for negligent PPATs or notaries, and civil protection for defrauded creditors underscores systemic risk. The study proposes a Unified Certificate Verification System (SVST), mandatory digital verification, blockchain-based registration, land title insurance, and legal reform to enforce due diligence and institutional accountability. It concludes that Indonesia’s current framework fails to ensure legal certainty and justice for financial institutions, and urgent structural reform is needed to enhance transparency, minimize transactional risks, and restore public trust in land-based financial transactions.